2021
DOI: 10.1128/mra.00604-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Acinetobacter junii Strain INC8271, Isolated from a Patient with Metastatic Cancer and Bacteremia

Abstract: Acinetobacter junii INC8271 was isolated from a cancer patient with polymicrobial bacteremia after biliary stent placement. The complete genome sequence consisted of a chromosome of 3,530,883 bp (GC content, 38.56%) with 3,377 genes, including those encoding 74 tRNAs and 18 rRNAs, and two intact prophage sequences. No antibiotic resistance genes were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nonetheless, several reports have shown it can be an opportunistic human pathogen ( 2 6 ). Some studies suggest it can cause bacteremia or ocular infections in humans ( 3 , 4 , 6 ). Yet, other studies indicated it can also cause infections in animals ( 7 9 ).…”
Section: Observationmentioning
confidence: 99%
“…Nonetheless, several reports have shown it can be an opportunistic human pathogen ( 2 6 ). Some studies suggest it can cause bacteremia or ocular infections in humans ( 3 , 4 , 6 ). Yet, other studies indicated it can also cause infections in animals ( 7 9 ).…”
Section: Observationmentioning
confidence: 99%